A typical band-shaped calcific keratopathy with keratocyte changes. Issue 5 (May 1982) - Dark, A J; Proctor, J
Abstract : The clinical features of a patient with atypical band keratopathy are described. Histochemical and electron probe analyses indicate that the granular deposits in Bowman's layer contain calcium and phosphate. An unusual feature in this patient was the presence of severe keratocyte degeneration; its possible role in the pathogenesis of this condition is discussed. Exfoliation of the calcified Bowman's layer appears to have been the basis for severe attacks of recurrent ocular pain.